Postcolonial Imagination and Postcolonial Theory: Indigenous Canadian and Australian Literature Fighting for (Postcolonial) Space - Polak, Iva (Array, 2005)
The paper focuses on the shifting and problematic term of "postcolonial literature" when applied to indigenous writing in Canada and Australia. Discussion offers a whole range of versatile definitions of postcoloniality and postcolonial theory from the publication of The Empire Writes Back (1989) onwards relying on the works by the authors such as B. Ashcroft, G. Griffiths, H. Tiffin, V. Mishra, B. Hodge, S. Slemon, etc., as well as the reactions and alternative solutions coming from Indigenous writers such as Thomas King, Lee Maracle and Marie Battiste in Canada, and Mudrooroo and Ian Anderson, in Australia.